2015
DOI: 10.1111/ans.13067
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of re‐excision in wire‐guided wide local excision for early breast cancer: a Western Australian multi‐centre experience

Abstract: This study highlights factors that should make the surgeon more cautious for re-excision. Suspicion of DCIS, especially at the periphery of tumours, and a central tumour location increase risk. Lesion localization techniques play an important role in minimizing risk while maintaining cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Enabling surgeons to accurately assess the surgical margin and/or the breast cavity during breast‐conserving surgery may enable more effective removal of tumor . This could potentially reduce the number of patients requiring additional procedures, currently 20% to 30% . A number of techniques have been utilized for intraoperative surgical margin assessment, including frozen section histology, imprint cytology, intraoperative ultrasound and intraoperative specimen radiography; however, these techniques have not significantly reduced re‐excision rates .…”
Section: Introductionmentioning
confidence: 99%
“…Enabling surgeons to accurately assess the surgical margin and/or the breast cavity during breast‐conserving surgery may enable more effective removal of tumor . This could potentially reduce the number of patients requiring additional procedures, currently 20% to 30% . A number of techniques have been utilized for intraoperative surgical margin assessment, including frozen section histology, imprint cytology, intraoperative ultrasound and intraoperative specimen radiography; however, these techniques have not significantly reduced re‐excision rates .…”
Section: Introductionmentioning
confidence: 99%
“…If no tumor is found on the cut edge or within the margin, it is classified as a negative margin. Currently, ~20 -30% of patients undergo a re-excision procedure to remove additional tissue due to detection of an involved (positive or close) margin [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Final margin assessment is, however, generally only available postoperatively, from histopathological examination performed days after the surgery. It is reported that 20–30% of patients undergoing breast‐conserving surgery require a second surgery due to insufficient (known as positive) margins . Existing intraoperative assessment methods include frozen‐section histology, and imprint cytology; however, these methods are not widely used, typically add 25–35 min to the operating time, and are limited to assessing only a small portion of the margin .…”
Section: Introductionmentioning
confidence: 99%